2008
DOI: 10.1542/peds.2007-1029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pediatric Practice-Based Smoking Prevention and Cessation Intervention for Adolescents: A Randomized, Controlled Trial

Abstract: A pediatric practice-based intervention delivered by pediatric providers and older peer counselors proved feasible and effective in discouraging the initiation of smoking among nonsmoking adolescents for 1 year and in increasing abstinence rates among smokers for 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 38 publications
2
85
0
1
Order By: Relevance
“…68 Three of the trials trained counselors to provide intensive counseling and telephone follow-up. [92][93][94] Overall, these studies suggest that behavioral interventions improve cessation.…”
Section: Tobacco Intervention Research In the Past Decade And Researcmentioning
confidence: 81%
“…68 Three of the trials trained counselors to provide intensive counseling and telephone follow-up. [92][93][94] Overall, these studies suggest that behavioral interventions improve cessation.…”
Section: Tobacco Intervention Research In the Past Decade And Researcmentioning
confidence: 81%
“…[16][17][18][19] It is unknown, however, whether these findings are generalizable to younger patients, as there have been fewer studies among adolescents in primary care. 25,26 Existing studies suggest that primary care screening and brief interventions can positively impact adolescent health issues, such as tobacco use, [27][28][29][30] nutrition and physical activity, 31,32 and depression. 33,34 A large longitudinal study of 14-year-old primary care patients 26 found that screening and brief provider counseling significantly increased helmet use but did not reduce adolescent alcohol or drug use, suggesting the need to explore supplemental strategies to enhance effectiveness, such as the computerized education component that occurs before the provider visit in the cSBA system.…”
mentioning
confidence: 99%
“…2 Because adolescent health is so tightly linked to behavior, research has focused on strategies that promote positive behavioral choices. [3][4][5][6] A growing consensus recognizes that teaching driving techniques is not enough to affect adolescent driving safety; we also must influence driving-related attitudes and behaviors. 7 Incorporating the knowledge gained from addressing attitudes and actions for other adolescent behaviors into the driving context is a sound place to begin.…”
mentioning
confidence: 99%